The NORTh Europe HOStile access TAVI (NORTHOSTAVI) registry - Kefer, Joelle; Kobari, Yusuke; Briki, Rachid; Dubois, Christophe; De Roeck, Frederic; De Cock, Emmanuel; Pirlet, Charles; Aminian, Adel; Colas-Florial, Julie; Vanhaverbeke, Maarten; Guédès, Antoine; Bataille, Yoann; et al. (Frontiers in Cardiovascular Medicine, 2025)
Background-aimsComparisons between alternative access routes for transcatheter aortic valve implantation (TAVI) in patients with hostile vascular access are scarce. This study aimed to perform a head-to-head comparison of various techniques (percutaneous transaxillary [P-TAx], surgically-assisted transaxillary [S-TAx], transcarotid [TCar], percutaneous transluminal angioplasty-assisted transfemoral [PTA-TF], transbrachiocephalic [TBra], and transcaval [TCav]) with respect to the 30-day outcome of patients undergoing TAVI.MethodsNORTHOSTAVI (NORTh Europe HOStile access TAVI) was an international registry that included patients undergoing TAVI via various endovascular transarterial access routes in Northern European countries. The primary endpoint was the adjusted 30-day rate of composite overall mortality, disabling stroke, main access site-related major vascular complications, and major bleeding according to VARC-3 criteria.ResultsIn total, 531 patients were enrolled in the study across 14 centers. The main access routes were TCar (N = 183, 35%), P-TAx (N = 153, 29%), S-TAx (N = 79, 15%), and PTA-TF (N = 76, 14%), while TBra and TCav were used in 23 (4%) and 17 (3%) patients, respectively. Technical success was achieved in 95% of cases, 30-day overall and event-free survival rates were 97% and 91%, respectively, similar between groups. P-TAx, but not S-TAx or PTA-TF, was associated with an increased adjusted risk of overall stroke (adjusted OR: 4.21; 95%CI: 1.129–15.747; p = 0.003) compared to TCar. PTA-TF was associated with an increased adjusted risk of main access site-related major vascular complications (adjusted OR: 7.71; 95%CI: 1.367–43.554; p = 0.02) compared to TCar.ConclusionsThe NORTHOSTAVI registry showed that in patients with hostile iliofemoral anatomy, TAVI via various endovascular transarterial access route is efficient and safe.